Optimizing Online Learning Using Oceanvira E-Learning Application - Sasongko, Dimas Bayu (INFOKUM, 2022)
The Covid-19 pandemic caused learning activities to stop offline for some time and switch to using an online learning system to reduce the spread of the virus. Online learning has many challenges, among which the focus of cadets is less effective because the process of delivering material is not done directly or face-to-face. This study used descriptive qualitative research method. The subjects of this study were three hundred and twenty-six Sidoarjo Marine and Fisheries Polytechnic. Based on the results of the study, it shows that lecturers have carried out online learning activities well. This is indicated by the cadets' statements, that the lecturers can explain the material well and the cadets easily understand it. Lecturers also utilize technology well to support online learning. The results showed that most cadets have been able to use learning tools well so as to reduce the obstacles that occur during lectures. Effectiveness is a guideline for the success of a learning activity. The results showed that 41.1% of cadets felt 'quite' with the statement. The author interprets that informants still do not feel the benefits of the positive impact and also feel the negative impact of this online learning. The results of the study are (1) online learning activities take place interspersed with face-to-face learning approximately one to two times a week with the number of participants 50% of the class capacity. (2) Lecturers must increase creativity by using learning media that can make it easier for cadets to understand lecture material.